Effect of Biostimulants on Yield and Quality in Tomato - T Saraswathi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
An experiment was conducted to study comparative efficacy of growth regulators and panchakavya on growth, yield and biochemical constitution of tomato. It is well known that panchakavya plays a vital role in organic cultivation. Hence, the present experiment was laid out to determine the effect of this biostimulant on yield and quality in tomato. Recommended dose of fertilizers recorded highest yield. Next best results were obtained by combined spray of panchakavya (3%) + salicylic acid (100ppm) + nitrobenzene (150ppm); panchakavya (3%) alone and panchakavya (3%) + salicylic acid (100ppm). Results also revealed comparable performance of panchakavya over salicylic acid and nitrobenzene indicating, that, panchakavya can be utilized as an organic component to increase yield in tomato.